Exploring Parametric and Mechanistic Differences between Expi293FTM and ExpiCHO-STM Cells for Transient Antibody Production Optimization - Jing Zhou; Guoying Grace Yan; David Cluckey; Caryl Meade; Margaret Ruth; Rhady Sorm; Amy S. Tam; Sean Lim; Constantine Petridis; Laura Lin; Aaron M. D’Antona; Xiaotian Zhong (Antibodies, 2023)
Rapidly producing drug-like antibody therapeutics for lead molecule discovery and candidate optimization is typically accomplished by large-scale transient gene expression technologies (TGE) with cultivated mammalian cells. The TGE methodologies have been extensively developed over the past three decades, yet produce significantly lower yields than the stable cell line approach, facing the technical challenge of achieving universal high expression titers for a broad range of antibodies and therapeutics modalities. In this study, we explored various parameters for antibody production in the TGE cell host Expi293FTM and ExpiCHO-STM with the transfection reagents ExpiFectamineTM and polyethylenimine. We discovered that there are significant differences between Expi293FTM and ExpiCHO-STM cells with regards to DNA complex formation time and ratio, complex formation buffers, DNA complex uptake trafficking routes, responses to dimethyl sulfoxide and cell cycle inhibitors, as well as light-chain isotype expression preferences. This investigation mechanistically dissected the TGE processes and provided a new direction for future transient antibody production optimization.